Physical Characteristics of Processed Food Meatballs Based on Mussels (Anadara granosa) - Rusita, Youstiana Dwi; Shafira, Wynne Afra; Nasikin, M Ali (Poltekkes Kemenkes Gorontalo, 2023)
Seafood is great for consumption by various age groups because it is rich in protein, fat, vitamins and minerals. One of the seafood that is often used by the community is shellfish. Mussels (Anadara granosa) is a type of shellfish commonly eaten by Asian people because it has economic value and excellent nutritional content for consumption, especially a source of protein and minerals. One of the processed forms of mussels is meatball. The purpose of the study was to determine the results of physical quality (organoleptic and pH), chemical quality (fat and protein) in mussels meatballs (Anadara granosa). This types of research carried out quantitative research using descriptive. The test parameters are organoleptic test, pH test, protein content test using the biuret method and fat content test using the soxhletation method. The results of the organoleptic test showed a green-black color, a normal smell typical of meat, a normal taste for meatballs, a chewy texture and a pH of 6.807. The results of the protein content test in mussel meatballs were 2.972% and the fat content test had a level of 9.1186%. Based on the physical tests, mussels meatballs meet the criteria.